Burkitt lymphoma after adult liver transplantation: a case report and literature review - Zhang, Ji; Chen, Qing; Zhang, Shuhua (Frontiers in Oncology, 2024)
Preface and importanceBurkitt’s lymphoma (BL) is a relatively rare post-transplant lymphoproliferative disorder (PTLD), and there is currently limited research on the occurrence of BL following adult liver transplantation.Case introductionWe report a 45-year-old male who developed BL that rapidly progressed at seven years after left liver transplantation. The patient eventually abandoned treatment due to severe clinical complications.Clinical discussionBL is a highly invasive B-cell-derived non-Hodgkin lymphoma (NHL), with fast progression and easy involvement of the central nervous system. The current case had sporadic BL with atypical site of onset. After analysis, the investigators considered the possible development of tumor lysis syndrome (TLS) in the later stage of hospitalization, which is a more serious complication of BL. There is currently no unified treatment plan for adult BL.ConclusionBL is a relatively rare complication after liver transplantation, and its early detection and treatment are crucial. For advanced BL, attention should be given in preventing the occurrence of TLS. Further research and exploration are needed to determine the optimal treatment plan for adult BL.